Development of Video Based Interactive Learning Computer Assist Language Learning (CALL) to Improve Arabic Language Proficiency for Class IX MTsN 4 Bogor - Abdillah, Dedi; Arief, Zainal Abidin; Widyasari, Widyasari (Educational Researcher Journal, 2025)
Language is very much used to communicate, mother tongue is the first language mastered by a person. Meanwhile, a second language needs to be learned to be able to master it. At MTsN 4 Bogor, the second language included in the subjects is Arabic. Of the four competencies that must be mastered, there is one competency that is considered difficult to master, namely the competency to speak Arabic. To improve students' speaking competence, researchers developed Interactive Learning Videos. So the research method used is Research and Development (R&D). From the research results, it was found that interactive learning videos can be accessed offline and can be used on computers in the Language Laboratory room. For the test results of learning materials, learning media and learning design, the respective results obtained were {93.04%, 91% and 93%), where the respective expert test results were included in the very valid category. Meanwhile, the results of calculating the effectiveness of interactive learning videos obtained a result of 84.32%, which indicates that interactive learning videos are effective for improving Arabic speaking skills.